Insecurity and Foreign Direct Investment by Oil Multinationals in Nigeria: Niger-Delta in Focus - Akindoyo, Olorunsemi Akin (Kashere Journal of Politics and International Relations, 2025)
The study interrogates the dynamics of insecurity and its impact on Foreign Direct Investment (FDI) by multinational oil corporations in Nigeria’s Niger Delta, with a specific focus on Delta and Ondo States between 2017 and 2022. Framed within the Capability Theory, the research identifies oil theft, militant attacks, and kidnapping as strategic tools of economic warfare that deter investment and disrupt national revenue flows. Employing a mixed-methods approach, the study analyzed data from 200 questionnaires and 40 in-depth interviews alongside official records. Findings revealed a significant negative correlation between insecurity and FDI inflow, particularly through oil theft (B = 0.464, p = 0.001) and the killings of oil workers (B = 0.199, p = 0.001), corroborating the hypothesis that insecurity exacerbates capital flight and undermines operational sustainability. The study argues that these patterns reflect not just random criminality but a systemic resistance to marginalization and environmental degradation, with insecurity weaponized as a form of local bargaining. The implications are profound: international oil companies (IOCs) such as Shell and Chevron have begun divesting, resulting in over $1 billion in oil revenue losses in the first quarter of 2022 alone (NUPRC, 2022). The study concludes that resolving the FDI-insecurity nexus requires comprehensive reforms in environmental governance, resource allocation, and state capability to enforce law and order. A multi-dimensional strategy—including environmental remediation, inclusive governance, and community-based policing—is recommended to stabilize the investment environment and promote sustainable development.